1999
DOI: 10.1089/10430349950019011
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Plasmid DNA to Inflammation in the Lung after Administration of Cationic Lipid:pDNA Complexes

Abstract: Cationic lipid-mediated gene transfer to the mouse lung induces a dose-dependent inflammatory response that is characterized by an influx of leukocytes and elevated levels of the cytokines interleukin 6 (IL-6), tumor necrosis factor alpha (TNF-alpha), and interferon gamma (IFN-gamma). We have examined the contribution of plasmid DNA (pDNA) to this observed toxicity, specifically the role of unmethylated CpG dinucleotides, which have been previously shown to be immunostimulatory. We report here that complexes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(94 citation statements)
references
References 30 publications
3
89
0
2
Order By: Relevance
“…[39][40][41] Therefore, there may be considerable utility in finding an intravenous formulation for PEI which can deliver small quantities of plasmid not eliciting inflammatory responses, can be administered in lower volumes and infusion rates, and is effective in the presence of physiological salt and protein concentrations. The addition of an appropriate concentration of soluble protein such as serum albumin to PEI and plasmid DNA in PBS meets these needs for transfection of lung tissue via intravenous administration.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Therefore, there may be considerable utility in finding an intravenous formulation for PEI which can deliver small quantities of plasmid not eliciting inflammatory responses, can be administered in lower volumes and infusion rates, and is effective in the presence of physiological salt and protein concentrations. The addition of an appropriate concentration of soluble protein such as serum albumin to PEI and plasmid DNA in PBS meets these needs for transfection of lung tissue via intravenous administration.…”
Section: Discussionmentioning
confidence: 99%
“…It is more likely that other factors involved in the inflammatory cascade in the mice are unaffected by the methylation status of the plasmid DNA and may play a more important role in the overall inflammatory environment. In the period during which this manuscript was under revision a paper was published 6 describing similar studies in mice with analysis at day 1 after administration. They also noted that despite differences in cytokine levels between MpDNA:lipid and UMpDNA:lipid treated animals there was no significant difference in the inflammation score between the two groups when histopathological analysis was performed.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 The second-generation cationic lipid GL-67 displayed a higher transgene expression in an initial study, 46 but this result has not been confirmed in later studies, where maximal gene expressions comparable to those of DOTMA and UPC have been reported. 47 The high efficiency of PEI may be due to its high buffering capacity in the endosomal compartment, which leads to positively charged ions being trapped by the amines in PEI, enhanced osmolarity and subsequent endosomal rupture and escape into the cytoplasm. 18,27 The high efficiency may also be due to enhancement of transgene transport from the cytoplasm to the nucleus.…”
Section: After 24 H the Membranes Of Endosomal Compartments Filledmentioning
confidence: 99%